Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada STMKG (Sekolah Tinggi Meteorologi Klimatologi dan Geofisika) Pondok Aren Tangerang Selatan - Nurul Hani Azzahra; Alan Budi Kusuma (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Human resources are one of the important assets in a company. Therefore, so that employees obey and feel comfortable at work, companies need to do something to improve employee performance at work, namely by providing support in the form of work discipline and work environment. The method used is descriptive quantitative method. The sampling technique in this research was a saturated sample with a sample size of 65 people. Data collection techniques are carried out by observation, questionnaires and documentation. Based on the results of the simultaneous test, the F test is (57,140) > F table (3.15), proving that the Work Discipline and Work Environment variables together have a positive and significant influence on employee performance with the multiple linear regression equation Y = 3.639 + 0.173 X1 + 0.759.X2 and the coefficient of determination value is 0.648, it can be concluded that Work Discipline (X1) and Work Environment (X2) together have an influence contribution of 65% on Employee Performance (Y).